Efektivitas Intervensi Non-Farmakologis sebagai Upaya Menghentikan Kebiasaan Merokok - Safanda Tiara Fitri; Rizki Amalia Putri; Miftahul Maulidiyah; Novita Dewi; Rizma Salsa Salim; Dewi Nur Halisa; Bella Fevi Aristia; Alfulaila Alfulaila; Eka Putri Nurhidayah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Smoking is one of the leading causes of morbidity, premature death, and disability that can be prevented by various efforts. This article reviews various non-pharmacological interventions that are effective in reducing smoking behavior. The method used is to conduct a literature search from 10 journals. The results of the article review show that all methods used to stop smoking behavior have proven effective. The methods for stopping smoking that are widely used in this article are SFET, MHT, Making xylitol candy and nicotine candy, and counseling on efforts to reduce smoking cessation. This method can reduce the intensity of smoking and increase awareness of the dangers of smoking. In addition, the use of xylitol gum and education programs have also been shown to be effective in reducing smoking habits. An approach that involves family and community support, as well as appropriate counseling, is very important to increase individual knowledge and motivation to quit smoking. With the right combination of strategies, it is expected to reduce the prevalence of smoking and its negative impacts on public health.